Vulnerability and adaptation to climate change in the Canadian Arctic - Pearce, T; Smit, B (Academic Press, 2013)
Arctic ecosystems are already experiencing and responding to climate change. Inuit communities are highly dependent on the natural environment for their livelihoods, and hence are particularly sensitive to the effects of climate change. Community-based studies across the Canadian Arctic have identified several widespread vulnerabilities. Subsistence hunting is susceptible to changes in wildlife populations and access to hunting areas; permafrost degradation has implications for community infrastructure and for coastal erosion; changes in the availability of harvested food contribute an additional risk to people s health; the erosion of environmental knowledge and land skills enhances the vulnerability of Inuit hunters to climate risks; and economic opportunities may come with more shipping, but may be constrained by closed ice roads and limits on the sport hunting industry.